Drugs used in prostatic enlargement and lower urinary tract symptoms: unseen and overlooked effects on sexual health - Ashrafuzzaman, SM; Rahim, Muhammad Abdur; Latif, Zafar Ahmed (BIRDEM Medical Journal, 2019)
Benign prostatic hyperplasia (BPH) is one of the most common genitourinary complications in men over 50 years of age and typically presents with lower urinary tract symptoms (LUTS) and may need medical and occasionally surgical interventions. Few of them may only need advice on behavioral modification like less water intake after sunset, avoid tea, coffee after evening, avoid alcohol and less use of diuretics. The symptoms related to BPH or LUTS without any prostatic enlargement are incomplete voiding, frequency, intermittency, urgency, weak stream, straining and nocturia. For most patients with mild to moderate symptoms of BPH [International Prostate Symptom Score (IPSS) <8 or 8-19 respectively] monotherapy with an á-1-adrenergic antagonist remains initial treatment. The choice of specific á-adrenergic antagonist agent is generally based on cost and side effect profile. Other classes of medications include 5á-reductase inhibitors and phosphodiesterase (PDE) 5 inhibitors. In men who have mild to moderate symptoms of BPH and concomitant erectile dysfunction (ED), PDE-5 inhibitors are reasonable alternative. Now a days á-1-adrenoceptor blockers and 5á-reductase inhibitors are often combined to give a synergistic effect. A review of the current literature identified several adverse sexual side effects, including ED, decreased libido, orgasmic disorders and ejaculatory disorders. It is important to know the extent of these side effects, as the clinician and patient will need to decide the cost of improved voiding symptoms. The prime adverse effect is ejaculatory disorders including the absence of ejaculation. Clinical consideration for BPH/LUTS should include the elements of male sexual function, patient’s age and the characteristics and comprehensive effects of each group of drugs. Methodological bias in clinical studies, such as the subjective evaluation of the sexual side effect makes it difficult to determine the ideal drug for treatment. Men without ED or irritant symptoms who desire medical therapy but cannot tolerate á-1-adrenergic antagonists and do not have predominately irritant symptoms or concomitant ED, treatment with a 5á-reductase inhibitor is a reasonable. Treatment for 6 to 12 months is generally needed before prostate size is sufficiently reduced to improve symptoms. Symptoms are usually reversible, so drugs may need to be continued for long time or indefinitely under supervision of specialist. Birdem Med J 2019; 9(3): 240-247